Sustainability of Blood Pressure Reduction in Black Barbershops - Victor, Ronald G; Blyler, Ciantel A; Li, Ning; Lynch, Kathleen; Moy, Norma B; Rashid, Mohamad; Chang, L Cindy; Handler, Joel; Brettler, Jeffrey; Rader, Florian; Elashoff, Robert M (Circulation (New York, N.Y.), 2019)
We developed a new model of hypertension care for non-Hispanic black men that links health promotion by barbers to medication management by American Society of Hypertension-certified pharmacists and demonstrated efficacy in a 6-month cluster-randomized trial. The marked reduction in systolic blood pressure (BP) seen at 6 months warranted continuing the trial through 12 months to test sustainability, a necessary precondition for implementation research. We enrolled a cohort of 319 black male patrons with systolic BP ≥140 mm Hg at baseline. Fifty-two Los Angeles County barbershops were assigned to either a pharmacist-led intervention or an active control group. In the intervention group, barbers promoted follow-up with pharmacists who prescribed BP medication under a collaborative practice agreement with patrons' primary care providers. In the control group, barbers promoted follow-up with primary care providers and lifestyle modification. After BP assessment at 6 months, the intervention continued with fewer in-person pharmacist visits to test whether the intervention effect could be sustained safely for 1 year while reducing pharmacist travel time. Final BP and safety outcomes were assessed in both groups at 12 months. At baseline, mean systolic BP was 152.4 mm Hg in the intervention group and 154.6 mm Hg in the control group. At 12 months, mean systolic BP fell by 28.6 mm Hg (to 123.8 mm Hg) in the intervention group and by 7.2 mm Hg (to 147.4 mm Hg) in the control group. The mean reduction was 20.8 mm Hg greater in the intervention (95% CI, 13.9-27.7; P<0.0001). A BP <130/80 mm Hg was achieved by 68.0% of the intervention group versus 11.0% of the control group ( P<0.02). These new 12-month efficacy data are statistically indistinguishable from our previously reported 6-month data. No treatment-related serious adverse events occurred in either group over 12 months. Cohort retention at 12 months was 90% in both groups. Among black male barbershop patrons with uncontrolled hypertension, health promotion by barbers resulted in large and sustained BP reduction over 12 months when coupled with medication management by American Society of Hypertension-certified pharmacists. Broad-scale implementation research is both justified and warranted. URL: https://www.clinicaltrials.gov . Unique identifier: NCT 02321618.